Linguistic and cultural quiz as a tool for raising Interest in studying Russian as a Foreign Language - Vlasova K. V., Samodurova O. I. (The Topical Issues of the Humanities and Social Sciences: from Theory to Practice, 2024)
This article discusses the implementation and conduct of a linguistic and cultural quiz on Russian as a foreign language for foreign students. Examples of relevant questions and recommendations for organizing and evaluating the quiz are given.
Keywords: лингвострановедение; интерактивная форма обучения; interactive form of learning; linguistic and cultural studies; викторина; форма контроля знаний; иностранный (русский) язык; Key words: quiz; form of knowledge control; foreign (Russian) language